Marketing Management in Order to Maintain Public Trust in Islamic Boarding Schools : A Narrative Study at Minhajut Thullab Islamic Boarding School (Manajemen Pemasaran dalam Rangka Menjaga Kepercayaan Masyarakat terhadap Pondok Pesantren : Studi Naratif di Pondok Pesantren Minhajut Thullab) - Siti Aisyah; Nur Alim (Shautut Tarbiyah, 2022)
This article aims to analyze the marketing management practices of educational institutions at the Minhajut Thullab Islamic Boarding School, Andoolo Village, with 2 (two) main highlights, namely: 1) Islamic boarding school marketing management, and; 2) Islamic boarding school marketing strategy. This study uses a qualitative approach, with a narrative approach. Data collection techniques were carried out through interviews, observation and documentation. Data analysis through the process of data reduction, data presentation and drawing conclusions or data verification as well as data validity techniques through data triangulation (techniques, sources and time), extension of observations, and conducting Memberchecks. The results showed that: 1) Marketing management of educational institutions at Minhajut Thullab Islamic boarding school through the process of planning, organizing, directing and implementing processes, and monitoring processes 2) Strategies in marketing educational institutions at Minhajut Thullab Islamic boarding schools through visual media (brochures and billboards) , social media (Facebook, Instagram and Youtube) and through media lectures conducted by caregivers of Islamic boarding schools. This research suggests the need for Islamic boarding schools to design independent and digital-based marketing systems in accordance with the spirit of industry 4.0.Keywords: Marketing Management and Educational Institutions